PERSPEKTIF KARYAWAN : Faktor-faktor yang Mempengaruhi Naiknya Kinerja - Hadyati Harras; Endah Finatariani; Purwatiningsih Purwatiningsih (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Along with the times, there has been a shift in the perspective of organizational management, especially the involvement of human resources. In this century, HR is given a high position, including fulfilling satisfaction. This is done, because the owner of the company realizes that progress will only be achieved if HR maintenance is carried out very well. This study is interested in examining how performance is from the employee's point of view. This is intended so that all interests within the company can be accommodated, especially the interests of HR as the spearhead of the company. To follow up this research, a quantitative approach and regression analysis were used. The object of this research is Panin bank employees in South Tangerang City Region. The results of the study indicate that a good compensation system is a factor that greatly affects the increase in performance. The results of the descriptive analysis explain that employees consider compensation to be the core of a million reasons for wanting to work, willing to be ordered, accepting pressure, ready to sacrifice time and energy. So, if all the sacrifices that have been made for a whole month get a high appreciation, in this case the compensation is commensurate, then very good work productivity will be born.